PROCEDURAL UNFAIR WAGE DIFFERENTIALS AND THEIR EFFECTS ON UNETHICAL BEHAVIOR. - Grosch, Kerstin; Rau, Holger A. (Economic Inquiry, 2020)
In this paper, we investigate how payment procedures that are deemed unfair can spur unethical behavior towards innocent coworkers in a real‐effort experiment. In our Discrimination treatment, a highly unfair payment procedure with wage differentials, half the workforce is randomly selected and paid by relative performance whereas the remaining receives no payment. A joy‐of‐destruction game measures unethical behavior subsequently. Non‐earners in Discrimination destroy significantly more than in the non‐discriminatory control treatments. In Discrimination, unethical behavior is generally high for all non‐earners, independent of individual inequality aversion and relative performance beliefs. In the control treatments, inequality aversion is the main driver of destructive behavior.